How Can Employee Engagement Drive Sustainability? The Mediating Power of CSR and Ethical Leadership in the Philippine Hospitality Industry - Emmanuel P. Paulino; Reyman M. Gapas; Reynaldo J. Villegas; Ronald P. Romero (Journal of Business, Management, and Social Studies, 2026)
The primary goal of this research is to examine how employee engagement influences sustainable business practices within the Philippine hospitality industry. Specifically, it seeks to understand the roles of Corporate Social Responsibility (CSR) and ethical leadership as mediating factors that link engaged employees to long-term organizational sustainability. Adopting a rigorous quantitative design, this study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 285 frontline employees and HR managers across luxury and mid-tier hotels in Metro Manila, Philippines. Empirical findings reveal that employee engagement exerts a significant direct impact on corporate social responsibility (CSR) and ethical leadership behaviors. The mediation analysis further confirms that these two factors function as essential mechanisms that translate employee engagement into sustainable business outcomes. Consequently, the study highlights that fostering a motivated and ethically guided workforce is fundamental to enhancing both organizational responsibility and competitive performance. The study contributes to the existing body of knowledge in two distinct ways, beginning with its focus on geographic specificity by providing much-needed localized empirical evidence from the Philippines. This is particularly significant given that while hospitality is a pillar of the Philippine economy, it remains under-researched in the context of sustainable human resource management. Furthermore, the research introduces an integrated model that bridges the gap between engagement and sustainability, which are often studied in isolation. By positioning corporate social responsibility and ethical leadership as twin mediators, the study offers a holistic perspective on how “soft” human resource factors translate into “hard” competitive advantages for organizations.